2017
DOI: 10.1002/ange.201710940
|View full text |Cite
|
Sign up to set email alerts
|

Doppelt regioselektive asymmetrische C‐Allylierung von Isoxazolinonen: Iridium‐katalysierte N‐Allylierung mit nachfolgender Aza‐Cope‐Umlagerung

Abstract: Isoxazolinone sind biologischu nd synthetischi nteressante,d icht funktionalisierte Heterocyclen, die lange Zeit nichtinenantiomerenangereicherter Form über asymmetrische Katalyse zugänglichw aren. Neben dem Mangel an enantioselektiven Methoden ist die Funktionalisierung der Isoxazolinone oft durch Regioselektivitätsprobleme aufgrund der Konkurrenz mehrerer nukleophiler Zentren innerhalb der Heterocyclen erschwert. Hier beschreiben wir die erste regiound enantioselektive C-Allylierung von Isoxazolinonen. Diese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Moreover, we considered the option of an N-allylation with a subsequent [3,3]-rearrangement. [14b] However, substrate 8 [6] did not form 3aA under the reaction conditions (Scheme 2, bottom), no matter if trichloroacetamide was present or not.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we considered the option of an N-allylation with a subsequent [3,3]-rearrangement. [14b] However, substrate 8 [6] did not form 3aA under the reaction conditions (Scheme 2, bottom), no matter if trichloroacetamide was present or not.…”
Section: Methodsmentioning
confidence: 99%
“…[3,1,4] Recently, our group has reported a binary catalyst system consisting of a chiral Ir I complex [5] and an achiral Pd II salt, which allowed for the only reported catalytic asymmetric allylation of isoxazolinones (Scheme 1, middle). [6][7][8] Isoxazolinones are synthetically versatile heterocycles prepared in one step from β-ketoesters and hydroxylamine, [7b] and can for instance be transformed into biologically interesting β-aminoacid derivatives. [9] It was shown that this allylation proceeded via an Ir catalyzed regioselective N-allylation forming a branched allyl isomer which then undergoes a [3,3]-rearrangement, thereby enforcing an (E)-configuration of the C=C double bond.…”
mentioning
confidence: 99%
“…As an important expansion of scope for the Pd-catalyzed asymmetric allenylic [4+ +1] cycloaddition, we examined isoxazolinones,another biologically and synthetically interesting class of heterocycles, [13] to react with allenyl acetates.S of ar only few enantioselective methods for the asymmetric synthesis of isoxazolinones with C-centered electrophiles has been reported because of the difficulty in regiocontrol of different competitive nucleophilic centers (C,N ,O ). [14] Pleasingly,t he desired product 6 was accessed smoothly in 64 %w ith 7:1d .r.a nd 88 % ee in the presence of ap lanarchiral Pd catalyst (Scheme 5).…”
Section: Entrymentioning
confidence: 98%